Modernization of "Polimir" Process of High-Pressure Polyethylene Production at "Tomskneftekhim" Company - Klimov I. G.; Koval E. O.; Pestryakov A. N. Aleksey Nikolaevich; Mayer E. A. Eduard Aleksandrovich (2012, 2012)
Title screen